Subalternity, antagonism, autonomy : constructing the political subject - Modonesi, Massimo, 1971- (Reading Gramsci., 2014)
"In this bold and innovative book, Massimo Modonesi weaves together political theory and political practice by relating the concepts of subalternity, antagonism and autonomy to contemporary movements in Latin America and elsewhere."--Page 4 of cover